Nigerian LIS Academic and Scholarly Publishing Experience: Challenges and the Way Forward. Issue 1 (14th October 2022) - Obinyan, Oluwatoyin O.; Tella, Adeyinka
Abstract: The study examined Nigerian Library and Information Science, LIS academics and scholarly publishing experience: challenges and the way forward. A purely qualitative method was adopted using interview as a data collection instrument. The population of study comprised LIS academics from two LIS departments in two universities at the South–south region of Nigeria. Four objectives were developed to guide the study. The results reveal that LIS academics publish mostly for promotion, to improve the knowledge in their chosen discipline, keep themselves abreast of the development in LIS discipline, LIS academics scholarly publication experience range from beginners up to twelve years with publications in various reputable LIS outlets. LIS academics face the challenges of heavy workload, inadequate experience, and lack of knowledge of relevant scholarly publishing outlets, and increasing rate of electronic journals due to advancement in ICT among others. To overcome the challenges, incentives should be provided to motivate LIS academics to engage in scholarly publishing, sponsorship of LIS academics to attend international conference to gain confidence, knowledge and experience on scholarly publishing, allocate money for staff to support their scholarly publishing, a compilation of a unified standard list of journals that should be a guide on where to get published.